Living Hadith: Study of Transmission and Transformation of the Practice of Reading the Hadith of the Prophet Muhammad saw: Living Hadis: Studi Transmisi dan Transformasi Praktik Pembacaan Hadis Nabi Muhammad saw - Qadri, Abdul (Jurnal Living Hadis, 2023)
Not only as a second guide after the Qur'an, some Muslims treat the hadith of Ṣaḥīḥ al-Bukhāri in a unique and unusual manner; read in turns without explanation like the practice of reciting the Koran. In contrast to reading the Koran, which has religious values (worship, intercession, and others), there are no hadiths or the Koran that encourage the reading of hadiths. Using a social history perspective, the paper attempts to explore how the early emergence and development of the practice of reading hadith Ṣaḥīḥ al-Bukhāri in the Islamic world and how hadith (text) exists in the social practices of Muslims. As a practice that spatializes the sound of hadith texts (living hadis), this paper finds four forms of classification of transmission-transformation of hadith reading practices: 1). Hadith reading in the tradition of hadith transmission, has emerged from the beginning as a method of teaching and spreading hadith. 2). The reading of hadiths in healing practices in the 3H century, was carried out by Ahmad bin Mashur al-Ramadi. 3). In the 7H/13M century, reading appeared and the use of Ṣaḥīḥ al-Bukhāri as a protective practice in the social space, as an intermediary for the personification of the Prophet to God in answering the problems faced by Muslims. 4). The reading and use of Ṣaḥīḥ al-Bukhāri developed into a routine annual tradition in the 8H/14AD centuries; Rajab; Sha'ban; Ramadan; dry months. Done with big celebrations to get goodness, blessings, piety, reward, intercession of the Prophet, revive the Prophet's Sunnah, preserve ancestral traditions, hospitality, and efficacious intermediaries of prayer.